2001
DOI: 10.1021/jf0007030
|View full text |Cite
|
Sign up to set email alerts
|

Revising the Role of pH and Thermal Treatments in Aflatoxin Content Reduction During the Tortilla and Deep Frying Processes

Abstract: Naturally aflatoxin-contaminated corn (Zea mays L.) was made into tortillas, tortilla chips, and corn chips by the traditional and commercial alkaline cooking processes. The traditional nixtamalization (alkaline-cooking) process involved cooking and steeping the corn, whereas the commercial nixtamalization process only steeps the corn in a hot alkaline solution (initially boiling). A pilot plant that includes the cooker, stone grinder, celorio cutter, and oven was used for the experiments. The traditional proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 10 publications
(15 reference statements)
0
36
1
3
Order By: Relevance
“…The decrease in aflatoxin content depends on the time and temperature combination. Moreover, alkaline cooking and steeping of corn for the production of tortillas reduces aflatoxin by 52% (Torres et al, 2001). Hameed (1993) reported reductions in aflatoxin content of 50–80% after extrusion alone.…”
Section: Effects Of Processing On Aflatoxinmentioning
confidence: 99%
“…The decrease in aflatoxin content depends on the time and temperature combination. Moreover, alkaline cooking and steeping of corn for the production of tortillas reduces aflatoxin by 52% (Torres et al, 2001). Hameed (1993) reported reductions in aflatoxin content of 50–80% after extrusion alone.…”
Section: Effects Of Processing On Aflatoxinmentioning
confidence: 99%
“…13 In another report, this traditional nixtamalization process reduced levels of AFB 1 by 94% and AFB 1 -8,9-dihydrodiol by 93%. 14 Roasting is considered one of the most effective methods of reducing aflatoxin levels in certain commodities, such as peanuts and coffee in particular, with average reductions in the aflatoxin content of peanuts ranging from 45% to 83% following dry roasting being reported.…”
mentioning
confidence: 95%
“…Several studies reported that significant levels of aflatoxin were removed by hydrated sodium calcium aluminosilicates (Phillips et al 1990, Phillips et al 1995, Grant and Phillips 1998, Phillips 1999, Huwig et al 2001. Heat and pH were also used by Guzman et al (2001) to reduce aflatoxin in corn tortilla with at moderate success at alkaline pHs (>10), achieving a range of degradation of 51-84%, depending on the food product. Despite this multitude of aflatoxin detoxification methods, the need remains for more effective, environmentally friendly and less hazardous means of aflatoxin detoxification.…”
Section: Introductionmentioning
confidence: 99%